2014
DOI: 10.3329/jles.v8i0.20133
|View full text |Cite
|
Sign up to set email alerts
|

An Introduction to Morphology of the Reproductive System and Anatomy of Hen’s Egg

Abstract: The present study was designed to investigate the morphology of reproductive system and egg anatomy of the domestic hen (Gallus domesticus L.). The system consists of oviduct and ovary. The oviduct consists of infundibulum, magnum, isthmus, uterus and vagina which are sole distributor for making nutrition enriched egg. The anatomy of egg revealed that there are calcareous eggshell, shell membranes, egg white, vitelline membrane, egg yolk, and germinal disc. The fertilized egg showed a concentric circle around … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 35 publications
4
11
0
1
Order By: Relevance
“…3). These results were in agreement with the results of Rahman et al (2009) and Rahman (2013) in which they reported that the Chalaza and chalaziferous layer ropes of protein fibers consisted of protein secreted from the glandular cells of the neck region of the infundibulum. These results proved the results of Khokhlov (2008) and Essam et al (2016) who recorded that the presence of tubular glands distributed within the connective tissue lamina propria of infundibulum in the oviduct of mature hen and Balady duck.…”
Section: Glands Of Neck (Infundibulum)supporting
confidence: 93%
See 1 more Smart Citation
“…3). These results were in agreement with the results of Rahman et al (2009) and Rahman (2013) in which they reported that the Chalaza and chalaziferous layer ropes of protein fibers consisted of protein secreted from the glandular cells of the neck region of the infundibulum. These results proved the results of Khokhlov (2008) and Essam et al (2016) who recorded that the presence of tubular glands distributed within the connective tissue lamina propria of infundibulum in the oviduct of mature hen and Balady duck.…”
Section: Glands Of Neck (Infundibulum)supporting
confidence: 93%
“…All structural components of the laid egg are produced from the oviduct, except the yolk which formed from the ovum. The oviduct itself is a long tubular structure consisting of five functionally distinct parts (infundibulum, magnum, isthmus, shell gland or uterus, and vagina) (Rahman, 2013). After ovulation, the ovulated ovum is trapped by the action of the fimbriated region of the infundibulum.…”
Section: Introductionmentioning
confidence: 99%
“…Oviduct explants were placed immediately in DMEM/Ham’s F-12 medium (Biochrom AG, Berlin, Germany) supplemented with 5% fetal bovine serum (FBS, Biochrom), 2% chicken serum (Sigma–Aldrich, Steinheim, Germany), Penicillin/Streptomycin (P/S; 100 U/ml, 100 mg/ml) (Biochrom), 2.5 ug/ml Amphotericin B (Biochrom) and 1% of non-essential amino acids (Biochrom). The magnum represents the largest part of the oviduct ( Rahman, 2014 ) and was previously reported in chickens to express both α2,3 as well as α2,6 linked sialic acids ( Mork et al, 2014 ), and therefore were speculated that it would be susceptible to avian as well as more human-adapted IAV. The magnum part was manually cut into small rings of 1–2 mm as previously described ( Mork et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…of the eggshell membranes), the uterus (formation of calcified eggshell), and the vagina (oviposition or egg laying). Following ovulation, the ovum passes through the entire length of the oviduct, where the constituents of the egg are secreted and deposited from respective parts of the oviduct (Iwasawa et al, 2010;Rahman, 2013;Vijayakumar et al, 2014).…”
Section: Morphological Changes Of Reproductive Organs During Egg Formmentioning
confidence: 99%